PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE NUMBERED HEADS TOGETHER(NHT) UNTUKMENINGKATKAN KETERAMPILAN BERBICARA SISWA KELAS IV MIS AL-MUHSININ RIMBA MELINTANG - Jasmawati, Jasmawati; Kurniaman, Otang; Antosa, Zariul (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract: The use of appropriate learning models in the learning process will support the success of students in the learning process. The use of appropriate learning model that does not cause low ability students in mastering the learning materials. The purpose of this study is to improve students' speaking skills class IV MIS Al-Muhsinin Rimba Melintang in learning Indonesian. This research was conducted at MIS Al-Muhsinin Rimba Melintang. This research is a classroom action research. The instrument used in this study is the observation sheet activities of teachers and students as well as the performance of the test sheet. Furthermore, to determine the effectiveness of cooperative learning model Numbered Heads Together (NHT) against their speaking ability trials conducted to 25 students, by means of a speaking test. From the test results obtained by an increase in students' speaking skills reaches 88% with very good category.Key Words: Cooperative type Numbered Heads Together (NHT),Speaking Skills